2020
DOI: 10.21203/rs.3.rs-16985/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early essential newborn care is associated with increased breastfeeding: a quasi-experimental study from Sichuan Province of Western China

Abstract: Background: Breastfeeding is critical to promote maternal and child health in a short and long term. China has set national targets to further improve the exclusive breastfeeding rate. We aimed to examine associations between the provision of early essential newborn care (EENC) and breastfeeding outcomes among full-term vaginally delivered neonates in the first six months of life.Methods: We conducted a quasi-experimental study in eight maternal and children’s hospitals in Mianyang City and Deyang City in Sich… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Our study showed that mother-newborn SSC was associated with increased early initiation breastfeeding rate and rst-breastfeeding duration, which were highly consistent with previous studies [23][24] . SSC may activate the oxytocinergic system, and the elevated concentration of oxytocin in postpartum mother in turn promotes the lactation and prolonged breastfeeding duration 25 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that mother-newborn SSC was associated with increased early initiation breastfeeding rate and rst-breastfeeding duration, which were highly consistent with previous studies [23][24] . SSC may activate the oxytocinergic system, and the elevated concentration of oxytocin in postpartum mother in turn promotes the lactation and prolonged breastfeeding duration 25 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that mother-newborn SSC was associated with increased proportions of early initiation breastfeeding and a longer duration of first-breastfeeding -findings that are highly consistent with previous studies [27,28]. SSC may activate the oxytocinergic system, and the elevated concentration of oxytocin in postpartum mothers in turn promotes lactation and prolonged breastfeeding duration [29].…”
Section: Discussionsupporting
confidence: 91%
“…In China, EENC during vaginal deliveries has been performing since 2016 and contributed to increased rates of exclusive breastfeeding and improved maternal and neonatal health [4,6,15], while the evidence during cesarean deliveries remains lacking. The objective of this multicentered randomized controlled study is to evaluate the effectiveness of EENC for cesarean section newborns on exclusive breastfeeding rates and early initiation of breastfeeding rates in China.…”
Section: Discussionmentioning
confidence: 99%
“…EENC is a package of simple evidence-based and cost-effective interventions delivered around birth including thoroughly drying a newborn immediately after birth, delayed cord clamping, immediate and sustained skin-to-skin contact (SSC), initiating exclusive breastfeeding, and routine care (newborn eye care, vitamin K 1 , immunizations, weighting, and examinations) [3,4]. Implementation of EENC has been demonstrated to increase rates of exclusive breastfeeding at discharge, 3 months and 6 months of age, and reduce neonatal intensive care unit admissions, admissions with hypothermia and sepsis [5,6].…”
Section: Introductionmentioning
confidence: 99%